Pakistan : Seventh Review Under the Extended Arrangement and Modification of Performance Criteria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2015)
This paper discusses Pakistan's Seventh Review Under the Extended Arrangement and Modification of Performance Criteria (PCs). All end-March 2015 quantitative PCs were achieved, as well as the indicative target (IT) on cash transfers under the Benazir Income Support program. The IT on federal tax revenue was missed by a small margin, reflecting legal challenges to some of the tax measures and the negative impact of lower global commodity prices. The authorities have taken action to improve revenue and remain on track to meet the end-June 2015 fiscal deficit target. The IMF staff supports the authorities' request for modifications of the end-June net international reserves PC, and completion of the seventh review under the arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet